2017
DOI: 10.1136/bmjopen-2017-017584
|View full text |Cite
|
Sign up to set email alerts
|

Junior doctor psychiatry placements in hospital and community settings: a phenomenological study

Abstract: ObjectivesThe proportion of junior doctors required to complete psychiatry placements in the UK has increased, due in part to vacant training posts and psychiatry career workforce shortages, as can be seen across the world. The aim of this study was to understand the lived experience of a Foundation Year 1 junior doctor psychiatry placement and to understand how job components influence attitudes.DesignThe study was conducted using a cross-sectional qualitative phenomenological approach.SettingHospital and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…3,9,11,23 Authors of a recent systematic review declared that ‘Psychiatry as a career has been negatively regarded and unpopular among medical students’ and, as a consequence, ‘about 3.6% of British graduates decide on a career in psychiatry whereas 6% are needed.’ 9 Evidence from other studies indicates that perceptions about psychiatry may be influenced by experiences at medical school (including the type and amount of teaching), at foundation school, and during undergraduate and postgraduate placements. 10,24,25 However, a survey of medical students, aged 18 to 37 years, found that age was not significantly associated with having rated psychiatry in the top three most interesting specialties. 25 Moreover, surveys of UK medical graduates' career intentions between 1974 and 2009 found little variance among medical schools in the proportion reporting psychiatry as a first-choice long-term career, albeit females were slightly more likely to report this than males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,9,11,23 Authors of a recent systematic review declared that ‘Psychiatry as a career has been negatively regarded and unpopular among medical students’ and, as a consequence, ‘about 3.6% of British graduates decide on a career in psychiatry whereas 6% are needed.’ 9 Evidence from other studies indicates that perceptions about psychiatry may be influenced by experiences at medical school (including the type and amount of teaching), at foundation school, and during undergraduate and postgraduate placements. 10,24,25 However, a survey of medical students, aged 18 to 37 years, found that age was not significantly associated with having rated psychiatry in the top three most interesting specialties. 25 Moreover, surveys of UK medical graduates' career intentions between 1974 and 2009 found little variance among medical schools in the proportion reporting psychiatry as a first-choice long-term career, albeit females were slightly more likely to report this than males.…”
Section: Discussionmentioning
confidence: 99%
“…7 Extant literature, predominately survey-based, indicates that cultural and institutional biases against psychiatry influence junior doctors' specialty choice and are a phenomenon, to a greater or lesser extent, internationally. [9][10][11] However, to our knowledge, research has not been carried out to examine the likelihood of actual application to psychiatry training, given doctors' sociodemographic and educational background, medical education performance, and medical school and foundation school attended.…”
mentioning
confidence: 99%
“…High levels of stress amongst FY doctors have been identified nationwide [24] and those undertaking psychiatry placements have highlighted their uncertainty with working with patients with mental illness [25]. The combination of personal vulnerabilities and influences from mentally unwell patients, especially those with SMI, may therefore be overwhelming, affecting overall performance that declines during their placement [26].…”
Section: Discussionmentioning
confidence: 99%
“…40 Another reason for the lack of change in attitudes could be the specific components of the psychiatry clerkship. Recently, a number of contextual clerkship factors, such as interpersonal skills training related to patient management, 41 educational models like student-run clinics to increase medical students' perceived knowledge and comfort with psychiatry 42 , and enthusiastic and positive clinical staff encouraging the students' social integration 43 , have been proposed as influential in furthering students' long-term positive attitude towards psychiatry. Thus, efforts to improve attitudes towards psychiatry may require more than just one two-hour lecture.…”
Section: Limitationsmentioning
confidence: 99%